2015
DOI: 10.1063/1.4928218
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and magnetic properties of Mn and Fe-doped Co3O4 nanoparticles

Abstract: Mn and Fe-doped Co3O4 nanoparticles were prepared by a simple precipitation method. The synthesized particles were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), UV-Vis absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, and vibrating sample magnetometer (VSM) techniques. XRD analysis showed the cubic structure of Co3O4. SEM and TEM images confirmed the formation of interconnected nanoparticles. Mn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 26 publications
8
32
0
Order By: Relevance
“…These characteristics peaks for crystalline spinel metal oxides can shi by several cm À1 , and can be ascribed to the change in the surface strain or defects owing to the incorporation of Mn into the ZnCo 2 O 4 crystal structure. [32][33][34][35] The lack of distinct separate or characteristic peaks for the separate oxides are in accordance with the XRD results. FTIR spectroscopy is an important technique to identify the stretching and bending vibrations of different materials.…”
Section: Structural Studiessupporting
confidence: 81%
See 1 more Smart Citation
“…These characteristics peaks for crystalline spinel metal oxides can shi by several cm À1 , and can be ascribed to the change in the surface strain or defects owing to the incorporation of Mn into the ZnCo 2 O 4 crystal structure. [32][33][34][35] The lack of distinct separate or characteristic peaks for the separate oxides are in accordance with the XRD results. FTIR spectroscopy is an important technique to identify the stretching and bending vibrations of different materials.…”
Section: Structural Studiessupporting
confidence: 81%
“…[32][33][34] The phonon modes (three F 2g , an E g , and an A 1g mode) for MnCo 2 O 4 occur at similar positions. 35 The broad peaks obtained obscure the various modes, and the broadness can be attributed to the nano-size of the materials (see TEM analysis section).…”
Section: Structural Studiesmentioning
confidence: 99%
“…[7,10,33,34]. Further more, similar results were observed for B doped [35] and Fe doped [36] Co3O4 films. According to the study of Wang S. et al [33] optical absorption and accordingly transmission property are deeply relative to the valence state of the cobalt oxide.…”
Section: Optical Properties Of the Filmsupporting
confidence: 81%
“…In recent years, performance values of metal oxides have been tried to be increased by introducing various dopants [22]. Stella et al has reported that Fe doped on his C o3O4 has caused contraction for particle size compared with undoped and Mn doped films, Mn and Fe implantations have resulted in expansion of absorption in the visible section and there has been a shift in the forbidden energy range [23]. Kerli has reported that Bo doped on his Co3O4 film which he produced by spray method has distorted the crystal form, changed the forbidden energy range and increased the optical transmittance values [24].…”
Section: Introductionmentioning
confidence: 99%
“…On a comparable approach, doping Co 3 O 4 can also enrich the electronic conductivity by modifying the electronic structure of the nanoparticle. This has been evidenced from the studies reported such as, nitrogen doped Carbon/Co 3 O 4 ; Mn and Fe doped Co 3 O 4 ; Zn doped Co 3 O 4 ; Cd doped porous Co 3 O 4 [26] and Sulphur‐doped Co 3 O 4 nanowires .…”
Section: Introductionmentioning
confidence: 99%